Effect of different drying methods on the protein and product quality of hairtail fish meat gel - Hu, Y.; Que, T.; Fang, Zhongxiang; Liu, W.; Chen, S.; Liu, D.; Ye, X. (Taylor & Francis, 2013)
Three different methods, namely hot air drying (HA), microwave vacuum drying (MV), and vacuum freeze drying (FD), were employed to investigate the effect of drying method on the quality of hairtail fish meat gel. Compared with HA and MV, FD samples showed a better quality in terms of moisture content, water absorption index, and water solubility index, and had the highest overall acceptance in sensory evaluation. FD preserved the protein from degradation and formed an ordered porous microstructure. The nitrogen fraction assay revealed that protein was degraded into 40–100 kDa fragments during drying in HA, which was almost not affected by MV and FD. Overall, FD was the most suitable method for drying of meat gel made from hairtail, followed by MV and HA.